Development of a Cat Behaviour Issues Assessment Scale (CABIAS) Assessing Problem Behaviours in Cats - Kevin McPeake; Andrew Sparkes; Charlotte Billy; Sarah Endersby; Jean François Collin; Xavier De Jaeger (Animals, 2023)
Problem behaviours in cats, such as urine marking, scratching, fear, and problems of cohabitation between cats, can present a potential welfare problem for those affected cats and have a negative impact on the human–animal bond. The aim of this study was to develop a Cat Behaviour Issues Assessment Scale (CABIAS) for caregivers to assess these common problem behaviours in cats, and to investigate aspects of the validity and reliability of the CABIAS. The CABIAS uses an index score as a scoring system combining aspects of the frequency and intensity of the problem behaviour. An electronic survey was developed, and 384 households, each with two participants able to observe the cat’s behaviour, were recruited for the study. The participants were asked to record their cat’s behaviour independently at weekly intervals over a 6-week period. A FELIWAY Optimum diffuser (containing a commercial feline pheromone complex) was provided to half of the participants, to be used during part of the study. The participants were subdivided into four groups according to whether a problem behaviour was present (or not) and whether the pheromone diffuser was provided (or not). The results demonstrated that the index scores for each problem behaviour had very high inter-rater reliability. There was a high correlation between the index scores and the impact the problem behaviours had on the caregivers. In those cats with a declared problem behaviour where the product was used, a reduction in index scores was observed over the duration of the study. The CABIAS was shown to exhibit satisfactory validity, reliability, and sensitivity to change in the current study, suggesting that it may be valuable as a tool for assessing and monitoring scratching, inter-cat cohabitation, urine marking, and fear in cats. The CABIAS could be used by veterinarians and behaviourists to assess these problem behaviours in individual cats and monitor responses to treatment. The CABIAS could also be considered as a research tool to assess the efficacy of interventions aimed at improving these problems.